Dysregulation of NF-κB-Associated LncRNAs in Autism Spectrum Disorder - Honarmand Tamizkar, Kasra; Badrlou, Elham; Aslani, Termeh; Brand, Serge; Arsang-Jang, Shahram; Ghafouri-Fard, Soudeh; Taheri, Mohammad (Frontiers in Molecular Neuroscience, 2021)
Autism spectrum disorder (ASD) is a long-standing neurodevelopmental condition with prominent effects on social behavior of affected children. This disorder has been linked with neuroinflammatory responses. NF-κB has been shown to affect these responses in the orbitofrontal cortex of patients with ASD, thus being implicated in the pathogenesis of ASD. We measured expression of some NF-κB-associated lncRNAs and mRNAs (DILC, ANRIL, PACER, CHAST, ADINR, DICER1-AS1, HNF1A-AS1, NKILA, ATG5 and CEBPA) in the peripheral blood of ASD kids vs. healthy children. Expression quantities of ADINR, ANRIL, DILC, NKILA and CHAST were meaningfully higher in ASD cases compared with healthy kids (Posterior Beta = 1.402, P value < 0.0001; Posterior Beta = 2.959, P value < 0.0001; Posterior Beta = 0.882, P value = 0.012; Posterior Beta = 1.461, P value < 0.0001; Posterior Beta = 0.541, P value = 0.043, respectively). The Bonferroni corrected P values for these lncRNAs remained significant except for CHAST and DILC. Expression levels of other genes were not considerably different between cases and controls. Expressions of ATG5, DICER-AS1 and DILC were correlated with age of ASD patients (P < 0.0001). Among ASD cases, the most robust correlation has been detected between ADINR and NKILA (r = 0.87, P < 0.0001). Expression of none of genes has been correlated with age of healthy children. Among this group of children, expression levels of ADINR and CHAST were robustly correlated (r = 0.83, P < 0.0001). ANRIL had the greatest AUC value (AUC = 0.857), thus the best diagnostic power among the assessed genes. NKILA ranked the second position in this regard (AUC = 0.757). Thus, NF-κB-associated lncRNAs might partake in the pathogenesis of ASD.